Increasing the performance of continuous compression moulding by local pressure adaption - Piott, Florian; Krämer, Andreas; Lück, André; Hoffmann, Leo; Mitschang, Peter; Drummer, Dietmar (Advanced Manufacturing: Polymer and Composites Science, 2021)
Continuous compression moulding (CCM) is an efficient process for manufacturing endless fibre-reinforced thermoplastic composites, so called organic sheets. The semi-finished products are fully impregnated and consolidated and can be thermoformed into complex 3D-geometries. Applications benefit from excellent weight-specific features as well as functional integration. Nevertheless, limited production speed and lower than acceptable manufacturing quality are still a challenge, especially with the use of high shrinkage polymers. Hence, porosities and defects due to pressure drops inside the laminate during impregnation and solidification can cause degradation in material properties. With the integration of an active adaptive pressing tool and an inline pressure measurement system, the process can be optimised towards guided impregnation and improved pressure distribution. A calculation method based on the B-factor method by Mayer has been adapted for the CCM process in order to enhance the tool design. Both, production speed as well as organic sheet quality can be improved with the optimised processing system presented in the following work.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Continuous compression moulding; impregnation; organic sheet; solidification